222k views
4 votes
4 point3. What is the solution of the system of equations below?2x + 3y = 7x + y = 3O (1,2)(2,1)0 (4-1)(4,1)

1 Answer

6 votes
Solution of a system of equations

We want to find the value of x and y that satisfy both equations:

2x + 3y = 7

x + y = 3

We are going to solve it using the Elimination Method.

Elimination Method

We want to find an equation with only one variable based on both given equations.

We are going to add both sides of them.

In that addition we want that the term with x is 0.

In order to do it we transform the second equation multiplying it by -2, because

2x - 2x = 0x

Step 1: transforming the second equation

We multiply both sides of the second equation by -2:

x + y = 3

-2(x + y) = -2 · 3

↓ since -2(x + y) = -2x - 2y and -2 · 3 = -6

-2x - 2y = -6

Then we have the equations:

2x + 3y = 7

x + y = 3

2x + 3y = 7

-2x - 2y = -6

Step 2: adding both equations

Now we add each side of both equations:

2x + 3y = 7

-2x - 2y = -6

_________

0x + 1y = 1

Then, simplifying the result:

y = 1

Step 3: finding x value

We replace y by 1 on any of both original equations:

x + y = 3

↓ since y = 1

x + 1 = 3

↓ taking 1 to the right side

x = 3 - 1

x = 2

Step 4: ordered pair

In an ordered pair we wirte first the x value and then the y value:

(x, y)

(2, 1)

Answer: B. (2, 1)

User Xhark
by
5.6k points